Analisis Kepuasan Penghuni Perumahan Batara Terhadap Infrastruktur Perumahan Batara Di Kota Gresik - Caroline, Jenny; Shallahuddin, Mohammad Hanafi; Gunawan, Gunawan (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2024)
Batara Housing is a housing managed by PT Bumi Persada Hijau which is located in Sirnoboyo Village, Benjeng District, Gresik. This housing is an example of housing that was built with a rural concept in one area to improve facilities in the housing. So that, PT Bumi Persada Hijau could improve the facilities. This study aimed to measure the level of satisfaction felt by residents of Batara Housing and find out what they were the main improvements in the housing. To determine the level of satisfaction of Batara Housing Residents, the researcher compared the value of interests and services provided from the results of processing and analyzing the questionnaires distributed. The researcher conducted validity and reliability tests with statistical calculation tools to find out if the questionnaire used in this study was following the provisions. The researcher used five variables, namely building design, facilities and infrastructure, rates/prices, guarantees against surrounding problems, location conditions, and social environmental conditions. From the results of research and analysis using the IPA method, the researchers got (1) the value of the level of satisfaction of residents of Batara Housing on infrastructure was 73% 100%, which meant that consumers were not satisfied with the services provided because it was still far from the expectations desired by housing residents, (2) for priority improvements so that services were getting better, PT Bumi Persada Hijau needed to make improvements, among others: building area, drainage system, landfills, building maintenance, and places of worship located in Quadrant I (Priority Improvement).